تأثير التحفيز على تطوير مهارة الحديث في اللغة الانجليزية - Ali, Marwa Mohsen; Alforjani, Zadma (Al-Qurtas, 2026)
Oral communication is considered one of the important skills that students need to learn. It enables us to contact with each other and convey our messages. It has been argued that motivation is considered a necessary factor that facilitates the process of learning. Its impact on language learning was a matter of interest to many English language learning scholars and researchers. Students who are interested and motivated to learn a language do not consider failing and will take part in the teaching and learning processes actively. They will work extremely hard to comprehend the material through reading, talking with friends, asking the teacher for guidance or advice from someone with more knowledge, and willing to learn on their own. This paper aims to investigate the attitudes of teachers and their students towards learning oral communication. It explores the relationship between being extrinsically and intrinsically motivated to learn speaking skills. The research sample consists of 5 male and female teachers from 4 secondary public schools in Libya. The different schools in this study were chosen randomly using stratified random sampling. The other sample was made up of 60 students who were studying at the same schools. A combination of quantitative and qualitative research methods was utilised to collect data. The findings revealed that there was a relationship between motivation and learning a language. It also suggests that the quality of learning oral communication could be higher overall, and that targeted support and motivation would benefit all students